(untitled) (Global Journal of Science Frontier Research, 2020)
Pseudomonas spp. is one of the widely studied bacterium for its versatility to be used for agricultural purposes as bioagent, biostimulant, biofertilizers or biopesticides. However, the dynamics of its efficacy varied from lab to field. The advanced biocontrol technologies have enabled better understanding of adaptability of selected Pseudomonas for field applications. In our study, we subjected P.putida (NBAII RPF9) strain to heat shock and salt shock followed by microarray analysis of the gene expression under both stresses when induced independently. Few genes were expressed under both conditions whereas some of them were newly reported stress tolerance genes. The quantification of selected stress tolerance genes revealed the level of fold change of these genes under stress and its role in conferring mitigation of heat and salt shock to P.putida (NBAII RPF 9). These techniques can be considered as major criterion in selection of a potential bacterial strain for agricultural applications.